The Role of Missing Lyrics Technique in Developing Listening Skills among Indonesian EFL Students - roni itkes; sam hermansyah; Sumarlin Rengko (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2026)
This study investigates the role of the Missing Lyrics technique in developing listening skills among Indonesian English as a Foreign Language (EFL) students. Listening remains one of the most challenging language skills for EFL learners, particularly in regional school contexts where exposure to authentic spoken English is limited. To address this issue, the study employed a quantitative pre-experimental design using a one-group pretest-posttest model. The participants were 19 eighth-grade students of SMP Negeri 2 Baranti, Sidenreng Rappang Regency, Indonesia, selected through purposive sampling. The treatment consisted of six instructional sessions using English songs with missing lyrics activities. Data were collected through listening tests administered before and after the treatment, as well as a questionnaire to examine students’ perceptions. The data were analyzed using descriptive statistics and a paired-sample t-test with IBM SPSS Statistics. The findings revealed a significant improvement in students’ listening performance, with the mean score increasing from 16.84 in the pretest to 73.95 in the posttest. The paired-sample t-test showed a significance value of 0.000, indicating that the improvement was statistically significant. Questionnaire responses also showed that students had positive perceptions of the technique, particularly in terms of motivation, focus, and classroom engagement. These findings suggest that the Missing Lyrics technique is an effective, enjoyable, and practical strategy for improving EFL students’ listening skills. The technique can serve as an alternative instructional method for teachers seeking to integrate authentic and student-centered listening activities into English classrooms.